2022
DOI: 10.1111/fog.12578
|View full text |Cite
|
Sign up to set email alerts
|

Marine‐climate interactions with the blue shark (Prionace glauca) catches in the western coast of Baja California Peninsula, Mexico

Abstract: Fishery and size data by sex of 28,110 blue sharks (Prionace glauca) from 2162 longline sets documented by observers on board 204 fishery trips from the industrial fleet based in Ensenada, Mexico during 2006–2016, were used to conduct a spatial–temporal analysis of the catch‐per‐unit‐effort (CPUE) and its relationship with climate indices along the west coast of the Baja California Peninsula. Catch length analysis by maturity groups indicated catches were composed mainly by juvenile females (58–199 cm TL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…This is most likely due to the seasonality of sets, as the research sets during the same period revealed similar catch composition. Further, nearly all LBG EFP sets occurred during the months of July through October, whereas the majority of the blue shark catch occurred later in the swordfsh season (November-January) when blue shark abundance increased off southern California (Hanan et al, 1993;Sepulveda and Aalbers, 2018;Godínez-Padilla et al, 2022).…”
Section: Lbg Efp Catchmentioning
confidence: 99%
“…This is most likely due to the seasonality of sets, as the research sets during the same period revealed similar catch composition. Further, nearly all LBG EFP sets occurred during the months of July through October, whereas the majority of the blue shark catch occurred later in the swordfsh season (November-January) when blue shark abundance increased off southern California (Hanan et al, 1993;Sepulveda and Aalbers, 2018;Godínez-Padilla et al, 2022).…”
Section: Lbg Efp Catchmentioning
confidence: 99%
“…In this context, the Generalized Additive Models (GAM) and Cross Wavelets are specific tools that help us to understand multiple variables in a same problem that can be ecological and economic approaches. Nowadays, this way of analysis has been widespread used in fisheries field (Godínez‐Padilla et al, 2022; Li et al, 2023; Ma et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the Generalized Additive Models (GAM) and Cross Wavelets are specific tools that help us to understand multiple variables in a same problem that can be ecological and economic approaches. Nowadays, this way of analysis has been widespread used in fisheries field (Godínez-Padilla et al, 2022;Li et al, 2023;Ma et al, 2023). This is crucial if our objective is to strengthen conservation policies and improve fisheries management in the region influenced by the Amazon River (Jongman et al, 1995;Pinaya et al, 2016).…”
mentioning
confidence: 99%
“…The blue shark Prionace glauca L. 1758 is one of the most abundant and widely distributed shark species (Nakano & Stevens, 2008), and has the highest capture rates on both incidental and directed fisheries (Bailleul et al, 2018;Campana et al, 2009;Compagno, 1984;Godínez-Padilla et al, 2016;Nakano & Stevens, 2008). Here the authors genetically analysed samples of P. glauca from the Mexican northeast Pacific Ocean to test the presence of MP in the species.…”
mentioning
confidence: 99%